The Influence of Celebrity Endorsement and Brand Image on Interest to Repurchase Wardah Beauty Products at University Of Mataram - Rusminah HS; Wahyunadi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to examine the effect of celebrity endorsement, brand image on the repurchase intention of wardah beauty products at the University of Mataram.Â This type of research is associative quantitative researth. The population in this study were all female students at the University of Mataram who had used wardah beauty products. Respondents in this study amounted to 120 respondents. The results of this study indicate that the celebrity endorsement variable (X1) has a positive but no significant effect on repurchasing interest in purchasing wardah beauty products. This is evidenced by the results of the t-test of the celebrity endorsement variable (X1), which is the t-count value of 0,066 where this value is smaller than the t-table of 1,980. The t-test criteria if sig (0,948) > 0,05 then the celebrity endorsement variable has no significant effect on repurchase interest in purchasing wardah beauty products, while the results of the brand image variable (X2) have a positive and significant effect on the repurchase interest of wardah beauty products. This is evidenced by the results of the t-test, namely that the t-count value is 2.335 where this value is greater than the t-table of 1.980. the t-test criteria if sig (0.021) < 0.05 then the brand image variable has a positive and significant effect on buying interest in wardahâ€™s beauty products at the University of Mataram